Dating Violence Among Rural Adolescents: Perpetration and Victimization by Gender - Taylor, Sarah (Journal of interpersonal violence, 2022)
Adolescent dating violence (ADV) is a serious concern with various negative impacts on adolescent development. Research on ADV has predominantly been conducted in urban areas and has generally focused on physical and sexual forms of violence. The purpose of this study was to assess prevalence rates of various forms of ADV by gender in the rural context. A convenience sample of rural adolescents responded to an online survey. In total, 131 responses were used for this study. Participants reported perpetration and victimization experiences of physical abuse, sexual abuse, threatening behavior, relational aggression, verbal abuse, and cyber dating abuse. Descriptive statistics and chi-square analyses were used to determine gender differences in proportion and frequency of ADV. Results reveal that various forms of ADV are occurring in the rural context, with many of both males and females reporting perpetration and victimization. Overall, verbal and cyber ADV are the most common. Gender analysis reveals that males were significantly more likely to be victimized by physical abuse victimization, whereas females were significantly more likely to be victimized by sexual abuse. Though the proportion of adolescents reporting ADV were high in this study, most participants reported lower frequencies of ADV. Results support the urgent need in rural areas for education and prevention that target physical, sexual, and psychological components of healthy relationships. Rural dating violence prevention efforts must emphasize the importance of mutual respect across gender, rather than solely presenting this lesson to males in a traditional gendered manner. Results also suggest the need for rural areas to adopt comprehensive sex education that details sexual relationships that are consensual and healthy.